The surface energy balance of a polygonal tundra site in northern Siberia – Part 1: Spring to fall. - Langer, Moritz; Westermann, Sebastian; Muster, Sina; Piel, Konstanze; Boike, Julia (PANGAEA, 2012)
In this article, we present a study on the surface energy balance of a polygonal tundra landscape in northeast Siberia. The study was performed during half-year periods from April to September in each of 2007 and 2008. The surface energy balance is obtained from independent measurements of the net radiation, the turbulent heat fluxes, and the ground heat flux at several sites. Short-wave radiation is the dominant factor controlling the magnitude of all the other components of the surface energy balance during the entire observation period. About 50% of the available net radiation is consumed by the latent heat flux, while the sensible and the ground heat flux are each around 20 to 30%. The ground heat flux is mainly consumed by active layer thawing. About 60% of the energy storage in the ground is attributed to the phase change of soil water. The remainder is used for soil warming down to a depth of 15 m. In particular, the controlling factors for the surface energy partitioning are snow cover, cloud cover, and the temperature gradient in the soil. The thin snow cover melts within a few days, during which the equivalent of about 20% of the snow-water evaporates or sublimates. Surface temperature differences of the heterogeneous landscape indicate spatial variabilities of sensible and latent heat fluxes, which are verified by measurements. However, spatial differences in the partitioning between sensible and latent heat flux are only measured during conditions of high radiative forcing, which only occur occasionally.
Heat fluxes and surface radiation measurements from Samoylov Island, Lena Delta, Siberia, April to September 2007
Keywords: Heat Flux, latent; Heat Flux, sensible; HEIGHT above ground; Long-wave downward radiation; Long-wave upward radiation; MULT; Net radiation; Net radiometer, Kipp & Zonen, NR Lite; Radiometer, Kipp & Zonen, CNR 1; Samoylov_Island; Samoylov Island, Lena Delta, Siberia; Short-wave downward (GLOBAL) radiation; Short-wave upward (REFLEX) radiation; Time in days